Respostas
respondido por:
2
Resposta:
Explicação passo-a-passo:
a)
= a/2+2a/3
MMC (2,3)= 6
= (3a +2.2a)/6
= (3a+4a)/6
= 7a/6
b)
=4m/5 -1m/2
= 4m/5 - m/2
MMC (5,2)= 10
= (2.4m - 5m)/10
=(8m - 5m)/10
= 3m/10
c)
= 1t/3-2t
= t/3 - 2t
MMC = 3
= (t - 3.2t)/3
= (t - 6t)/3
= - 5t/3
respondido por:
1
Resposta:
a)7a/6 b)3m/10=0,3m c)-5/3t
Explicação passo-a-passo:
Tirando o m.m.c. de cada par de números, temos:
a)m.m.c.(2,3)=6
Então: a/2 + 2a/3=(3a+4a)/6=7a/6
b)m.m.c.(2,5)=10
Logo: (2*4-5)m/10=(8-5)m/10=3m/10=0,3m
c)m.m.c.(3,1)=3
Então: (1-6)t/3=-5t/3
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás